2003
DOI: 10.1007/s00428-003-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor is a marker for syncytiotrophoblastic cells in testicular germ cell tumors

Abstract: The epidermal growth factor receptor (EGFR) has been implicated in the pathogenesis, therapy and prognosis of various tumor types. The aim of this study was to investigate EGFR expression in a large series of testicular germ cell tumors (TGCTs). A total of 88 TGCTs (37 of pure type and 51 of mixed type) comprising a total of 44 seminoma, 49 embryonal carcinoma, 32 yolk sac tumor, 28 teratoma and 7 choriocarcinoma components were immunostained for EGFR. EGFR reactivity was observed in the stromal cells of embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Pluripotent potential germ-cell neoplasms, like IGCNU, seminoma, and embryonal carcinoma, are labeled with antibodies against PLAP, c-KIT [12], OCT3/4 (POU5F1) [15], and CD30 [18]. On the other hand, for differentiated GCT, several growth factors, growth factor receptors, and transcription factors have been reported in neoplastic cells but with various frequencies and variable specificity [8,11,21]. This study confirmed the outstanding specificity of GPC3 to differentiated GCT, such as in "the double layer pattern", glandular structures of embryonal carcinoma encircled by a row of flattened YST cells [1,3], in MGCT in which OCT3/4 and GPC3 immunoreactivities were mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Pluripotent potential germ-cell neoplasms, like IGCNU, seminoma, and embryonal carcinoma, are labeled with antibodies against PLAP, c-KIT [12], OCT3/4 (POU5F1) [15], and CD30 [18]. On the other hand, for differentiated GCT, several growth factors, growth factor receptors, and transcription factors have been reported in neoplastic cells but with various frequencies and variable specificity [8,11,21]. This study confirmed the outstanding specificity of GPC3 to differentiated GCT, such as in "the double layer pattern", glandular structures of embryonal carcinoma encircled by a row of flattened YST cells [1,3], in MGCT in which OCT3/4 and GPC3 immunoreactivities were mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR staining data is consistent with previous reports by other authors ( Table 4). The expression of this marker has been mostly associated to NSGCTs and particularly prevalent in pure choriocarcinomas or the choriocarcinomatous components of mixed forms [11][12][13][14]. In our series, EGFR expression showed an inverse association with tumour response of borderline significance.…”
Section: Discussionmentioning
confidence: 67%
“…Hechelhammer [14] 88 and the seminomatous components of mixed tumours Izquierdo [17] 60 Heterogeneous (NSGCT and SGCT) KIT 100% SGCT (membrane staining) 32%…”
Section: Discussionmentioning
confidence: 99%
“…EGF receptor (EGFR) overexpression is seen in many solid tumours, but in GCTs no EGFR reactivity was detected in 44 seminomas or in 32 yolk sac tumours [51]. In teratomas 20/28 overexpressed EGFR, as did all seven choriocarcinomas [51]. These findings were confirmed in other studies.…”
Section: New Drugs and Targeted Therapymentioning
confidence: 65%
“…One study targeting the epidermal growth factor (EGF) pathway with gefitinib has stopped including patients, but the treatment results have not yet been published. EGF receptor (EGFR) overexpression is seen in many solid tumours, but in GCTs no EGFR reactivity was detected in 44 seminomas or in 32 yolk sac tumours [51]. In teratomas 20/28 overexpressed EGFR, as did all seven choriocarcinomas [51].…”
Section: New Drugs and Targeted Therapymentioning
confidence: 99%